PENGARUH BUDAYA ORGANISASI DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI (DINAS TENAGA KERJAA DAN TRNSMIGRASI KAB. PUNCAK JAYA) - yikwa, dale; Nu Graha, Andi; farida ni'matullah, onik (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2024)
Abstract This research aims to determine the influence of organizational culture and workload on employee performance. This research uses quantitative methods, using saturated sampling, namely 50 employees of the Dinas Tenaga Kerja dan Transmigrasi Kab. Puncak Jaya. The data analysis used is multiple linear regression. The research results show that organizational culture and workload can improve employee performance, organizational culture can improve employee performance, workload can improve employee performance. Suggestions for improving employee performance need to pay attention to the effectiveness with which organizational resources are used.